2016
DOI: 10.1016/j.taap.2015.12.020
|View full text |Cite
|
Sign up to set email alerts
|

A cellular model to study drug-induced liver injury in nonalcoholic fatty liver disease: Application to acetaminophen

Abstract: Obesity and nonalcoholic fatty liver disease (NAFLD) can increase susceptibility to hepatotoxicity induced by some xenobiotics including drugs, but the involved mechanisms are poorly understood. For acetaminophen (APAP), a role of hepatic cytochrome P450 2E1 (CYP2E1) is suspected since the activity of this enzyme is consistently enhanced during NAFLD. The first aim of our study was to set up a cellular model of NAFLD characterized not only by triglyceride accumulation but also by higher CYP2E1 activity. To thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
71
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 91 publications
9
71
0
Order By: Relevance
“…When obese individuals undergo weight-loss surgery, they exhibit a decrease in CYP2E1 activity concomitant with decreased body weight. The relationship between obesity and CYP2E1 may impact toxicology, as has been shown for the common drug acetaminophen in cultured cells treated with fatty acids 31 and in obese and non-obese humans 32 . In those cases, higher body fat and/or treatment of cells with free fatty acids resulted in higher CYP2E1 levels and higher production of the toxic quinoneimine metabolite N-acetyl-p-benzoquinone imine (NAPQI), resulting in more hepatotoxicity and mitochondrial dysfunction.…”
Section: Endogenous Role Of Cyp2e1mentioning
confidence: 98%
“…When obese individuals undergo weight-loss surgery, they exhibit a decrease in CYP2E1 activity concomitant with decreased body weight. The relationship between obesity and CYP2E1 may impact toxicology, as has been shown for the common drug acetaminophen in cultured cells treated with fatty acids 31 and in obese and non-obese humans 32 . In those cases, higher body fat and/or treatment of cells with free fatty acids resulted in higher CYP2E1 levels and higher production of the toxic quinoneimine metabolite N-acetyl-p-benzoquinone imine (NAPQI), resulting in more hepatotoxicity and mitochondrial dysfunction.…”
Section: Endogenous Role Of Cyp2e1mentioning
confidence: 98%
“…). We also determined the mRNA levels of apolipoprotein A4 (APOA4), since we recently found that APOA4 expression was a sensitive marker of lipid accumulation in HepaRG cells incubated with fatty acids (Michaut et al, ). In the present study, APOA4 expression was also modulated by BPA in a nonmonotonic manner with a significant increase observed at the 2 nM concentration (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because steatosis can be associated with oxidative stress (Begriche et al, ; Tariq et al, ), we also assessed the mRNA expression of the following genes: heme oxygenase 1 (HMOX1), NAD(P)H dehydrogenase quinone 1 (NQO1), nuclear factor of kappa light polypeptide gene enhancer in B‐cells 1 (NFKB1), heat shock 70 kDa protein 1A (HSPA1A also known as HSP70‐1A), glutathione S‐transferase alpha 1/2 (GSTA1/2), GSTA3, and tribbles pseudokinase 3 (TRIB3). TRIB3 was investigated because its mRNA expression can be markedly enhanced in different conditions of stress, including when the cellular stores of the antioxidant glutathione are reduced (Ord and Ord, ; Aubert et al, ; Michaut et al, ). The expression of these genes was however unchanged (data not shown), thus indicating that BPA did not induce significant oxidative stress in our experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, we used a 1 m m concentration of APAP unlike other studies, where higher concentrations have been used despite increased toxicity and those dosages are multiple folds higher than typically administered in patients (McGill et al, ; Michaut et al, ). Even with 1 m m APAP, protein secretion seemed to increase relative to cultures without APAP, probably due to the response to APAP or toxicity.…”
Section: Discussionmentioning
confidence: 99%